2009
DOI: 10.1016/j.firesaf.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of unbonded post-tensioned concrete slabs under fire conditions

Abstract: a b s t r a c tThis paper investigates the structural behaviour of unbonded post-tensioned one-way spanning concrete slabs in fire conditions. The slabs were simply supported and reinforced with 15.7 mm nominal diameter seven-wire mono-strand tendons. A nonlinear finite element model for the analysis of posttensioned unbonded concrete slabs at elevated temperatures was developed. The mechanical and thermal material nonlinearities of the concrete, prestressing tendon and anchorages have been carefully inserted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 12 publications
4
35
0
Order By: Relevance
“…The same failure mode was previously reported in the small-scale unbonded and bonded fire tests conducted by Bailey and Ellobody [1,2]. Detailed explanation of the cause of the splitting was provided previously by Ellobody and Bailey [13]. Briefly, when the temperature of the tendons increases the tendon starts to expand longitudinally causing partial relief of the compressive stresses, which then allows the lateral expansion to cause splitting at the weaker sections of the slab that contain the tendons.…”
Section: Parametric Studies and Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The same failure mode was previously reported in the small-scale unbonded and bonded fire tests conducted by Bailey and Ellobody [1,2]. Detailed explanation of the cause of the splitting was provided previously by Ellobody and Bailey [13]. Briefly, when the temperature of the tendons increases the tendon starts to expand longitudinally causing partial relief of the compressive stresses, which then allows the lateral expansion to cause splitting at the weaker sections of the slab that contain the tendons.…”
Section: Parametric Studies and Discussionsupporting
confidence: 54%
“…The stress-strain curves of the plastic and steel ducts were predicted based on data provided by the manufacturers. Following the finite element modelling presented in Reference [13], the measured values of thermal expansion coefficients for concrete with Limestone and Thames Gravel aggregates available in the literature [25,26] were used, instead of the values given in the code [15]. It was shown that the values for thermal expansion given in the code produced erroneous predictions for the structural behaviour.…”
Section: Finite Element Modelling Of the Small-scale Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because full-scale fire tests on actual or model UPT buildings, however badly needed, are unlikely to occur in the foreseeable future, research is currently restricted largely to using computational analysis tools [52,53] to study their response to fire. In general, these tools have not been validated against real fires in UPT concrete structures and their ability to accurately model various aspects of UPT concrete beams and slabs at elevated temperature is doubtful.…”
Section: Discussionmentioning
confidence: 99%
“…The developed numerical tool utilizes FE analysis with prestressing model employing tendon element. Ellobody and Bailey [9] studied the structural behaviour of unbonded post-tensioned one-way concrete slab at elevated temperature. A nonlinear finite element model was developed for the PT analysis of unbonded concrete slab in fire.…”
Section: Introductionmentioning
confidence: 99%